Aerobic exercise program with or without motor complexity as an add-on to the pharmacological treatment of depression - Study protocol for a randomized controlled trial - Neves, Lucas Melo; Silva-Batista, Carla; Marquesini, Raquel; Da Cunha, Telma Fátima; Dimateo, Elisa; Nascimento, Luciana; Moreira-Neto, Acácio; De Lima Miliatto, Angelo Corrêa; Das Chagas Mendes, Sheila; Saad, Flavia; Codogno, Jamile Sanches [UNESP]; Nunes, Renato Hoffmann; et al. (Springer Nature, 2018)
Background: Patients with major depression disorder presents increased rates of cognitive decline, reduced hippocampal volume, poor sleep quality, hypertension, obesity, suicidal ideation and behavior, and decreased functionality. Although continuous aerobic exercise (CAE) improves some of the aforementioned symptoms, comorbidities, and conditions, recent studies have suggested that performing aerobic exercise with motor complexity (AEMC) may be more beneficial for cognitive decline, hippocampal volume, and functionality. Therefore, this randomized controlled trial will compare the effects of CAE and AEMC on depression score, cognitive function, hippocampal volume, brain-derived neurotrophic factor expression, sleep parameters, cardiovascular risk parameters, suicidal behavior, functionality, and treatment costs in patients with depression. Methods/design: Seventy-five medicated patients with depression will be recruited from a Basic Healthcare Unit to participate in this prospective, parallel group, single blinded, superiority, randomized controlled trial. Patients with depression according to DSM-V criteria will be balanced and randomly assigned (based on depression scores and number of depressive episodes) to a non-exercising control (C), CAE, and AEMC groups. The CAE and AEMC groups will exercise for 60 min, twice a week for 24 weeks (on non-consecutive days). Exercise intensity will be maintained between 12 and 14 points of the rating of perceived exertion scale (~ 70-80% of the maximum heart rate). The CAE group will perform a continuous aerobic exercise while the AEMC group will perform exercises with progressively increased motor complexity. Blinded raters will assess patients before and after the intervention period. The primary outcome measure will be the change in depression score measured by the Montgomery-Asberg Depression Rating Scale. Secondary outcomes will include measures of cognitive function, hippocampal volume, brain-derived neurotrophic factor expression, sleep parameters, cardiovascular risk parameters, suicidal behavior, functionality, and treatment costs. Discussion: This study was selected in the call of public policy programs for the Brazilian Unified National Health System - PPSUS 2015. To our knowledge, this is the first pragmatic trial to test the effect of adding AEMC to the pharmacological treatment of patients with depression and to evaluate the possible reductions in depression symptoms and healthcare costs. Trial registration: Brazilian Clinical Trials Registry (ReBec) - RBR-9zgxzd - Registered on 4 Jan. 2017.
Keywords: Brain volume; Cardiovascular; Clinical trial; Cognitive function; Coordinative exercise; Depression; Metabolic syndrome; Neuroplasticity; Physical activity level